Risk assessment of temporary pacing for cardiac arrest after cardiopulmonary bypass-assisted cardiovascular surgery: A case-control study - Heng Wang; Li Shen; Qingwen Lin; Heng Yu; Yu Zhang; Luzheng Zhang; Yujin Sun; Song Xue (PLoS ONE, 2025)
Objective Cardiac arrest happens in 0.7%-5.2% patients after cardiovascular surgery, and cases with asystole or severe bradycardia need timely temporary pacing. However, routine temporary pacing wire insertion in cardiopulmonary bypass (CPB)-assisted cardiovascular surgery has been questioned for its noteworthy complications. This study aimed to quantify the risk of temporary pacing for cardiac arrest after CPB-assisted cardiovascular surgery. Methods 2326 patients undergoing CPB-assisted cardiovascular surgery were enrolled. Age, sex, body mass index, preoperative rhythm, operation type, ablation, CPB pump, cardioplegia type and volume, hypothermia, circulation, CPB time, aortic clamping time were compared between patients having and not having temporary pacing according to the indications by multiple logistic regression (MLR). A scoring system was developed based on the β parameters of identified independent risk factors in MLR analyses. The score cutoff was determined by the negative likelihood ratio to exclude the need of temporary pacing. Results 108 patients (4.6%) had temporary pacing. Old age (per year) (P < 0.001), preoperative atrial fibrillation (P < 0.001), long CPB time (per minute) (P = 0.017) contributed to the risk of cardiac arrest. Having mitral valve replacement (MVR) (P = 0.033), double valve replacement (DVR), MVR+tricuspid valvuloplasty (TVP) (P = 0.009), coronary artery bypass grafting (CABG)+MVR (P = 0.0495) (versus CABG) were independent risk factors. The scoring system, score = age (year)/40 + CPB time (min)/350+ [preoperative atrial fibrillation]×1, can quantitatively assess the associated risk with an area under receiver of characteristic (ROC) curve (AUC) of 0.74 (95% confidential interval 0.69–0.79) (P < 0.001). The negative likelihood ratio was < 0.1 when score≤1.138. Therefore, the cutoff of excluding temporary pacing was set as ≤1, which achieved a 0% false negative rate in our cases. Conclusion To minimize iatrogenic complications caused by unnecessary temporary pacing wire insertion, while ensuring patients with risks of asystole or severe bradycardia receive timely pacing, surgeons may identify cases with negligible risks of cardiac arrest through the scoring system.